PENTING NYA LITERASI DALAM MENINGKATKAN BERFIKIR KERITIS SISWA - Moch Ilham Auladana; Hana Rohmatul Ghofiroh; Rizqiyah Nur Ramadlany (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
In an era of advancing technology, critical thinking skills have become increasingly essential for managing and analyzing complex information, especially that obtained through social media and the internet. Literacy today not only includes technical abilities but also serves as a means to access accurate and relevant information. This article employs a literature review method by examining various previous studies and references to illustrate the relationship between digital literacy and critical thinking. The findings indicate that digital literacy plays a central role in enhancing critical thinking skills, particularly among students, by encouraging them to carefully filter information and make objective judgments. Digital literacy also helps prevent the spread of false information and hoaxes, while supporting individuals' moral, social, and cognitive development. In everyday practice, digital literacy teaches internet users not to easily trust viral information without verification, but instead to engage in critical analysis of the sources and content. Therefore, the development of digital literacy and critical thinking is crucial in shaping intelligent, wise, and responsible individuals in facing the challenges of the digital era.